The Genetic Variability of Floral and Agronomic Characteristics of Newly-Bred Cytoplasmic Male Sterile Rice - El-Namaky, R. (MDPI, 2018)
Male sterility enabled commercialization of heterosis in rice but low seed set remains a constraint on hybrid dissemination. We evaluated 216 F6 maintainer lines for agronomic and floral characteristics in augmented design and selected 15 maintainer lines, which were testcrossed with IR58025A. Five backcrosses were conducted to transfer cytoplasmic male sterility (CMS) to select maintainer lines. Newly-bred BC5:6 CMS lines were evaluated for outcrossing rates and agronomic characteristics. There were highly significant differences among 216 F6 maintainer lines for characteristics whose genotypic variance was higher than environmental variance. The phenotypic coefficient of variation was almost the same as the genotypic coefficient of variation, indicating that most phenotypic variation was due to genetics. There were highly significant differences among CMS lines for number of days to 50% flowering and maturity; stigma exertion; panicle exertion, length and weight; spikelet fertility; tillers per plant; plant height; grains per panicle; grain yield per plant; and 1000-grain weight, but not for pollen and panicle sterility during dry and wet seasons. Three CMS lines (CMS3, CMS12, and CMS14), exhibited high outcrossing rates (56.17%, 51.42% and 48.44%, respectively), which had a highly significant, positive correlation with stigma exertion (0.97), spikelet opening angle (0.82), and panicle exertion (0.95).